1982
DOI: 10.1207/s15327752jpa4604_11
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Smoking Behavior

Abstract: Investigated the relationship between selected personality measures and the initiation and maintenance of smoking behavior. The Eysenck Personality Questionnaire (EPQ), the State-Trait Personality Inventory (STPI) and a Smoking Behavior Questionnaire were administered to 955 students (603 females; 352 males). Smokers had significantly higher scores than Nonsmokers on the EPQ Extraversion, Neuroticism and Psychoticism scales, and lower scores on the Lie Scale. Female Smokers had higher STPI Trait Anxiety scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
1
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 15 publications
1
73
1
3
Order By: Relevance
“…As example we cite a number of studies published in the last decades, which showed a strong relation between tobacco consumption and neuroticism and extraversion. 16,26,27 However, other works did not confirm, or confirmed only partially, such associations. 7,20,28 The association between smoking and psychoticism (P) has been shown in several studies carried out lately, 16,17,27,28 however, the mechanisms responsible for the associations between personality and smoking have not been elucidated.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…As example we cite a number of studies published in the last decades, which showed a strong relation between tobacco consumption and neuroticism and extraversion. 16,26,27 However, other works did not confirm, or confirmed only partially, such associations. 7,20,28 The association between smoking and psychoticism (P) has been shown in several studies carried out lately, 16,17,27,28 however, the mechanisms responsible for the associations between personality and smoking have not been elucidated.…”
Section: Introductionmentioning
confidence: 87%
“…15,27,35 However, some works have not confirmed such an association. 36,37 Today, data found in the literature are still conflicting.…”
Section: Smokers X Non-smokersmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies published in previous decades showed a relationship between smoking and neuroticism. (9,15) However, this association was not detected in some studies. (10,16) Nevertheless, in contrast with the extroversion factor, the relationship between neuroticism and smoking is more consistent and seems to have grown considerably during recent decades.…”
Section: Introductionmentioning
confidence: 90%
“…(8) In previous decades, most studies demonstrated that smokers tend to get higher scores in extroversion, compared with nonsmokers. (9,10) However, in some studies, this association was not confirmed. (11)(12)(13)(14) The association between smoking and extroversion has decreased in recent decades, possibly because smoking has become a socially undesirable habit in many countries.…”
Section: Introductionmentioning
confidence: 91%